2003
DOI: 10.1177/154411130301400508
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Paracoccidioidomycosis of the Mouth: an Emerging Deep Mycosis

Abstract: Oral fungal infections (mycoses) have come into particular prominence since the advent of infection with Human Immunodeficiency Virus (HIV), and recognition of the Acquired Immune Deficiency Syndrome (AIDS), as well as the phenomenal increase in world travel with increased exposure to infections endemic in the tropics. Paracoccidioidomycosis is a rare mycosis worldwide but common in Brazil and some other areas in Latin America. It can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…According to previous reports, these organs are the most common organs involved in PCM (Almeida et al , 2003; Verli et al , 2005; Vieira and Borsatto-Galera, 2006). We found that almost half of our PCM cases (41.9%) were diagnosed in the odontology pathology laboratory, which indicates that the oropharyngeal mucosa is frequently affected by this disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to previous reports, these organs are the most common organs involved in PCM (Almeida et al , 2003; Verli et al , 2005; Vieira and Borsatto-Galera, 2006). We found that almost half of our PCM cases (41.9%) were diagnosed in the odontology pathology laboratory, which indicates that the oropharyngeal mucosa is frequently affected by this disease.…”
Section: Discussionmentioning
confidence: 90%
“…This difference may be explained by a hormone protective factor in women. The presence of estrogen receptors in P. brasiliensis inhibits the transformation from the mycelial phase to the yeast parasitic phase of the fungus (Borges-Walmsley et al , 2002; Almeida et al , 2003; Vieira and Borsatto-Galera, 2006; Bousquet et al , 2007). If there is a hormone protective factor, then postmenopausal women should become more susceptible to PCM.…”
Section: Discussionmentioning
confidence: 99%
“…The infection occurs through the inhalation of conidia, which convert into yeasts in the lungs, causing benign and transient lesions. It may progress into an acute form or, more frequently, reactivate later as a chronic and insidious disease ( Restrepo, 2000 ; de Almeida, 2005 ; Laniado-Laborin, 2007 ), which disseminates to many different organs and tissues, particularly the skin, oral cavity, pharynx, larynx, upper gastrointestinal tract, lymph nodes, adrenal glands, and central nervous system ( Tuder et al, 1985 ; Do Valle et al, 1993 ; Almeida et al, 2003 ; de Almeida, 2005 ; Restrepo et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%